Stably coating loose and electronegative thin layer on anion exchange membrane for efficient and selective monovalent anion transfer - Zhang, H.; Ding, R.; Zhang, Y.; Shi, B.; Wang, J.; Liu, Jian (Elsevier BV, 2017)
© 2017 Elsevier B.V. Herein, a novel thin electronegative layer with loosely porous structure is fabricated through interfacial polymerization of benzene-rich monomer (2,5-diaminobenzenesulfonic acid (DSA) or 3,5-diaminobenzoic acid (DMA)) and cross-linker (trimesoyl chloride), using the blend of polyvinyl alcohol and quaternized-chitosan as base membrane. The base membrane achieves adequate fluxes for both monovalent and divalent anions but limits monovalent/divalent anions permselectivity to below 2.5. By comparison, the thin and porous surface layer endows the dual-layered membrane with only slight flux reduction of below 9.0% for monovalent anions, yet a 30.6% flux reduction for SO42 -based on Donnan-effect and steric effect. The effective intercept of SO42 -on membrane surface weakens its competitive transfer with Cl-, thus the Cl-/SO42 -permselectivity is significantly elevated by 472.2% from 1.8 to 10.3, which is even 36.3% higher than that of commercial Neosepta ACS. Furthermore, the antifouling potential and thermal/mechanical stabilities of the dual-layered membrane are improved assisted by the hydrophilic and electronegative features of coated layer and its covalent bonds with base layer. DSA and DMA, two analogous monomers, are utilized and compared to verify the universality of this nanostructure, helping to explore the structure-performance relationship.